GAMBARAN OBAT KEDALUWARSA, OBAT RUSAK DAN DEAD STOCK DI APOTEK X SEMARANG - Toyo, Eleonora; Suryo Wulan Amaliawati; Margareta Retano Priamsari; Ferika Indrasari (Journal Pharma Saintika, 2025)
Abstract Drug management is the most important thing in minimizing the occurrence of expired drugs, drug damage, and dead stock. This study aims to provide an overview and evaluate the occurrence of expired drugs, spoiled drugs, and dead stock at Pharmacy X Semarang in 2021. This research is a non-experimental study with a descriptive-analytical design, which is analyzed descriptively and qualitatively. The source of the data taken comes from electronic stock, written in the form of stock cards, bookkeeping of expired drugs, and damaged drugs. The results of this study indicated that tablet preparations had expired (0%), damaged drugs were (0.098%) and dead stock was (4.684%), so it was concluded that the percentage of damaged drugs and dead stock drugs did not match the research indicators. Therefore, medication planning tailored to drug needs must be validated, drug administration management must be improved, and drug acceptance systems must be strengthened.